2005
DOI: 10.1016/j.fishres.2005.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary assessment of the Falklands Patagonian toothfish (Dissostichus eleginoides) population: Use of recruitment indices and the estimation of unreported catches

Abstract: Longline fishing for Patagonian toothfish (Dissostichus eleginoides) has taken place in Falkland Island waters for over 10 years. This species was previously only caught as bycatch in the Loligo gahi and finfish trawl fishery. This paper presents a preliminary assessment of the Falkland Islands population of Dissostichus eleginoides using an age-structured production model (ASPM). Two models were investigated; one using a Beverton-Holt stock recruitment relationship and another using trawler CPUE based estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…Patagonian toothfish (Dissostichus eleginoides) is a large demersal, long-lived fish distributed widely in shelf and shelf-slope waters around Sub-Antarctic islands and both the east and west coasts of South America. There are assumed to be 5-6 stocks in the Antarctic (SC-CAMLR, 2007) and probably 2-3 on the east and west coasts of South America (Payne et al 2005). Globally, toothfish stocks have experienced high levels of exploitation due to high international demand for what is considered to be luxury seafood in the USA, Japan, and the EU (Catarci 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Patagonian toothfish (Dissostichus eleginoides) is a large demersal, long-lived fish distributed widely in shelf and shelf-slope waters around Sub-Antarctic islands and both the east and west coasts of South America. There are assumed to be 5-6 stocks in the Antarctic (SC-CAMLR, 2007) and probably 2-3 on the east and west coasts of South America (Payne et al 2005). Globally, toothfish stocks have experienced high levels of exploitation due to high international demand for what is considered to be luxury seafood in the USA, Japan, and the EU (Catarci 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, most studies deal with optimization of fishing efficiency and minimization of fishing impact, but bycatch data have rarely been used to learn about the biology and behaviour of the incidental species being caught, although several recent studies have shown the informative value of bycatch concerning food habits (Koen Alonso et al, 2001), feeding ecology (Rheeder and Sauer, 1998), and recruitment indices (Payne et al, 2005).…”
Section: Introductionmentioning
confidence: 99%